T cell-mediated targeted delivery of tadalafil regulates immunosuppression and polyamine metabolism to overcome immune checkpoint blockade resistance in hepatocellular carcinoma. Issue 2 (22nd February 2023) - Wang, Xiaobin; Zhang, Qiaoyun; Zhou, Jingwen; Xiao, Zecong; Liu, Jianxin; Deng, Shaohui; Hong, Xiaoyang; Huang, Wensou; Cai, Mingyue; Guo, Yongjian; Huang, Jingjun; Wang, Yong; et al.
Abstract : Background: Immune checkpoint blockade (ICB) monotherapy provides poor survival benefit in hepatocellular carcinoma (HCC) due to ICB resistance caused by immunosuppressive tumor microenvironment (TME) and drug discontinuation resulting from immune-related side effects. Thus, novel strategies that can simultaneously reshape immunosuppressive TME and ameliorate side effects are urgently needed. Methods: Both in vitro and orthotopic HCC models were used to explore and demonstrate the new role of a conventional, clinically used drug, tadalafil (TA), in conquering immunosuppressive TME. In detail, the effect of TA on M2 polarization and polyamine metabolism in tumor-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) was identified. After making clear the aforementioned immune regulatory effect of TA, we introduced a nanomedicine-based strategy of tumor-targeted drug delivery to make better use of TA to reverse immunosuppressive TME and overcome ICB resistance for HCC immunotherapy. A dual pH-sensitive nanodrug simultaneously carrying both TA and programmed cell death receptor 1 antibody (aPD-1) was developed, and its ability for tumor-targeted drug delivery and TME-responsive drug release was evaluated in an orthotopic HCC model. Finally, the immune regulatory effect, antitumor therapeutic effect, as well as side effects of our nanodrug combining both TA and aPD-1 were analyzed. Results: TA exerted a new role in conquering immunosuppressive TME by inhibiting M2 polarization and polyamine metabolism in TAMs and MDSCs. A dual pH-sensitive nanodrug was successfully synthesized to simultaneously carry both TA and aPD-1. On one hand, the nanodrug realized tumor-targeted drug delivery by binding to circulating programmed cell death receptor 1-positive T cells and following their infiltration into tumor. On the other hand, the nanodrug facilitated efficient intratumoral drug release in acidic TME, releasing aPD-1 for ICB and leaving TA-encapsulated nanodrug to dually regulate TAMs and MDSCs. By virtue of the combined application of TA and aPD-1, as well as the efficient tumor-targeted drug delivery, our nanodrug effectively inhibited M2 polarization and polyamine metabolism in TAMs and MDSCs to conquer immunosuppressive TME, which contributed to remarkable ICB therapeutic efficacy with minimal side effects in HCC. Conclusions: Our novel tumor-targeted nanodrug expands the application of TA in tumor therapy and holds great potential to break the logjam of ICB-based HCC immunotherapy.